Metastatic pattern discriminates survival benefit of primary surgery for de novo stage IV breast cancer: A real-world observational study. Issue 8 (August 2019) - Wang, Kang; Shi, Yang; Li, Zhu-Yue; Xiao, Ye-Lei; Li, Jie; Zhang, Xiang; Li, Hong-Yuan
Abstract: Introduction: Role of surgery in the management of de novo stage IV breast cancer (BC) remains controversial. We aimed to determine the survival benefit of primary surgery on the basis of metastatic pattern. Materials and methods: A retrospective cohort study based on the SEER database was conducted to identify patients with de novo stage IV BC diagnosed between 2010 and 2015. Patients were divided into surgery and non-surgery group, and propensity score weighting was used to balance clinicopathologic factors between groups. Results: Of 8142 de novo stage IV BC patients, 1891 (23%) cases were managed with surgery and 6251 (77%) cases were managed without surgery. There were 3821 all-cause deaths and 3291 BC specific deaths over a median follow-up of 22 months. The weighted 3-year overall survival (OS) for the surgery group was 54.5%, compared to 47.7% (P < 0.001) for the non-surgery group. The magnitude of the survival difference with surgery was significantly correlated with metastatic patterns (Pinteraction <0.05). Significant survival improvements in surgery group compared with non-surgery group were observed in patients with bone-only metastasis (adjusted HR = 0.83, P < 0.05) or multiple metastases with bone involved (adjusted HR = 0.76, P < 0.05), whereas survival inferiority of surgery was found for patients with multiple visceral organs-only metastases (adjusted HR = 2.08, P < 0.05). Conclusion: The survival benefit offered by surgery for de novo stage IV BC varies by metastatic patterns. Decisions for primary surgery of de novo stage IV BC patients should be tailored according to metastatic pattern.